Enhanced Catalytic Activity and Reusability of Porous Niobium Oxide for Esterification of Acetic Acid With Butanol - Balaga Viswanadham; Jhansi Pedada; Naresh Mameda; Balla Putrakumar (Journal of Chemistry, 2025)
Through this study, porous niobium (V) oxide catalysts for esterification of acetic acid with butanol to make butyl acetate are made and characterized. The catalysts were synthesized using a sol-gel method and characterized using X-ray diffraction (XRD), Raman spectroscopy, BET surface area analysis, and TPD acidity measurements. The XRD results confirmed the hexagonal structure of both fresh and regenerated catalysts, and the low-angle XRD analysis revealed the material’s porous nature. Raman spectroscopy showed the characteristic Nb-O-Nb stretching band at 698 cm−1, which was retained even at higher calcination temperatures. The catalytic performance was evaluated under various conditions, including different reactant mole ratios, catalyst amounts, and reaction temperatures. The optimal conditions were 1:2 mol ratio of acetic acid to butanol, 0.1 g of catalyst, and a reaction temperature of 120°C, achieving a maximum ester yield of 89%. The catalyst’s performance was superior to that of Al2O3, ZrO2, and bulk Nb2O5, highlighting the importance of the porous structure in providing a more significant number of active sites. Recyclability tests demonstrated that the catalyst maintains stable activity over five cycles, with only a slight decrease in yield. This stability is attributed to the retention of the porous structure and the high number of acidic sites at the optimal calcination temperature of 300°C.